2013
DOI: 10.1016/j.dnarep.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cellular signaling by 8-oxoguanine DNA glycosylase-1-initiated DNA base excision repair

Abstract: Accumulation of 8-oxo-7,8-dihydroguanine (8-oxoG) in the DNA results in genetic instability and mutagenesis, and is believed to contribute to carcinogenesis, aging processes and various aging-related diseases. 8-OxoG is removed from the DNA via DNA base excision repair (BER), initiated by 8-oxoguanine DNA glycosylase-1 (OGG1). Our recent studies have shown that OGG1 binds its repair product 8-oxoG base with high affinity at a site independent from its DNA lesion-recognizing catalytic site and the OGG1•8-oxoG c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 45 publications
(74 reference statements)
3
49
0
Order By: Relevance
“…However, among the Ser phosphorylation, that at amino acid 276 appears to be one of the most important, which is mediated by the catalytic subunit of protein kinase A and MSK1 (39, 5355). These events can be explained by the results from previous studies showing that OGG1 binds the 8-oxoG base at a substrate-independent site, and that 8-oxoG-induced conformational changes in the OGG1 molecule have allowed its physical interaction with and activation of RAS GTPases (16, 17), whose targets are RAF/MAPK and IP3Ks.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, among the Ser phosphorylation, that at amino acid 276 appears to be one of the most important, which is mediated by the catalytic subunit of protein kinase A and MSK1 (39, 5355). These events can be explained by the results from previous studies showing that OGG1 binds the 8-oxoG base at a substrate-independent site, and that 8-oxoG-induced conformational changes in the OGG1 molecule have allowed its physical interaction with and activation of RAS GTPases (16, 17), whose targets are RAF/MAPK and IP3Ks.…”
Section: Discussionmentioning
confidence: 94%
“…Changes in RAS-GTP levels were quantified using an Active RAS Pull-Down and Detection Kit (Pierce Biotechnology, Thermo Fisher Scientific) as described previously (16, 17). In brief, RAS-GTP from lung extracts and cell lysates (25 mM Tris-HCl, pH 7.5, 150 mM NaCl, 60 mM MgCl 2 , 1% NP40 and 5% glycerol) was captured by the RAS-binding domain of Raf1 (RBD) (29) immobilized on Glutathione Resin GST-RAF1-RBD.…”
Section: Methodsmentioning
confidence: 99%
“…In a similar way, also Myc-induced, retinoic acid-induced and androgen receptor-induced transcription has been proved [45][46][47] demonstrating that the transcriptional function of OGG1 is a much more general non canonical function than previously thought. OGG1, in complex with 8-oxoG free base, has been recently suggested to play a role in signal transduction as a new Guanine Exchange Factor (GEF) for Ras, Rac and Rho GTPases [48][49][50]. These findings open new completely unpredicted perspectives for this unusual DNA-repair enzyme in controlling gene expression.…”
Section: Unusual Involvement Of Ber Enzymes In the Regulation Of Genementioning
confidence: 98%
“…Because the repair-defective enzyme, like the wild-type enzyme, bound aconitase, the possibility was advanced that Ogg1 influences ROS-mediated signaling events downstream of mtDNA damage (80). In a related context, it has recently been shown that Ogg1 in complex with free 8-oxoguanine serves as a guanine exchange factor to activate Ras-mediated signaling (29), but whether this occurs in intact cells with ROS-induced mtDNA damage has not been established.…”
Section: Sentinel Functions Of Mtdna In Pulmonary Vascular Cellsmentioning
confidence: 99%